1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Atwood's Problem (pulley has mass)

  1. Apr 26, 2010 #1
    1. The problem statement, all variables and given/known data

    In the Atwood's machine shown below the masses of the blocks are ma = 3kg and mb = 2kg. The moment of inertia of this frictionless pulley about its axis is Ic = .6 kg m2 and its radius is Rc = .2m. Note that there is no slipping between the rope and the pulley.

    Find the accelerations of the blocks and the angular acceleration of the pulley

    this is the closest diagram i could find... the distance of the right block (I'll name it block 2 and the left block 1) above the ground is h.

    I thought of two ways to do this problem, but I wanted to try and use Newton's laws.
    I solved it using conservation of energy:
    EPot f - EPot i + Kfinal - Kinitial = 0
    so we know that:

    Kinitial = 0 (since its not moving yet)
    EPot f = m1(g)(h)
    EPot i = m2(g)(h)
    Kfinal = (1/2)m2v2 + (1/2)m1v2 + (1/2) Iw2

    then using vf2= vi2+2ah
    again vii = 0, so we can now replace every vf2 by 2ah

    at this point you have:
    m1(g)(h) - m2(g)(h) + (1/2)(ma)(2ah) + (1/2)(m1)(2ah) + (1/2)(I)(2ah/R2)

    Now cancel out all the h's and get:
    m1(g) - m2(g) + (1/2)(ma)(2a) + (1/2)(m1)(2a) + (1/2)(I)(2a/R2)

    After solving for a I got a = .49 m/s2 of the blocks (I'm not concerned with the angular acceleration right now)

    I think my answer is right but..
    Is there any way to use Newton's Laws... Maybe use the following?
    m2(g) - T2 = m2(a)
    T1 - m1(g) = m1(a)
    Or does this only apply for massless pulleys?
    I tried using it, and I get a different Answer... Also if someone could check my answer itd be nice
  2. jcsd
  3. Apr 27, 2010 #2
    M1g - T1 = M1a
    T2 - M1g = M2a
    torque (t) = T1R - T2R = Ia/r

    eliminate T1,T2

    M1g -M2g - (T1-T2) = (M1 + M2)a

    T1 - T2 = Ia/r^2

    M1g - M2g - Ia/r^2 = (M1 + M2)a

    a = (M1 - M2)g/(M1 + M2 + I/r^2 )

    massles pulley implies I = 0

    your answer 0.49 is correct using this approach
  4. Apr 27, 2010 #3
    Thanks for the help, I get it now... Just another question though... When we consider the pulley to massless does it mean that the tensions are equal? Since T1-T2=Ia/r2 Or am I jumping to a false conclusion? Thanks again
  5. Apr 27, 2010 #4
    True, if we consider the pulley massless T1 = T2. The difference is due to the fact that there is a friction force that turns the pulley.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook